x = 2+a and x = 2+b
=> (x-2-a)(x-2-b) = 0
x² -2x - xb - 2x +4 + 2b - ax + 2a + ab = 0
x² + x(-2 - b - a - 2) +4 + 2b + 2a + ab = 0
x² + x(- 4 - b - a) +4 + 2b + 2a + ab = 0
x² + x(- 4 - b - a) + (2 + a)(2 +b) = 0
x² - x( 4 + b + a) + (2 + a)(2 +b) = 0
2006-07-20 23:47:33
·
answer #1
·
answered by Brenmore 5
·
1⤊
0⤋
sum of the roots is (a+b+4) and the product (2+a)(2+b)
and so the equation
=x^2-(a+b+4)x+(2+a)(2+b)=0
2006-07-21 03:40:35
·
answer #2
·
answered by raj 7
·
0⤊
0⤋
aX^2 + bX + c=0.............divide by a
X^2 + (b/a)X + (c/a)=0
so, a+b= -(b/a)........@
ab = c/a.............#
if 2+a,2+b is the root...thn,
(2+a)+(2+b)= 4+a+b
= 4 - (b/a) .............from @
(2+a)(2+b) = 4+2a+2b+ab
=4 -2(b/a)+ (c/a) ..........from @ and #
so, X^2- (4 - (b/a))X +(4 -2(b/a)+ (c/a) )=0....thats all
2006-07-21 07:31:12
·
answer #3
·
answered by balu 1
·
0⤊
0⤋
the equation is
ax^2 + (4a-b)x + (4a -2b +c) =0
2006-07-21 03:31:35
·
answer #4
·
answered by abhinav 2
·
0⤊
0⤋
sorry,,, i didnt understand
2006-07-21 09:53:50
·
answer #5
·
answered by jai 2
·
0⤊
0⤋